2011
DOI: 10.1128/cvi.05379-11
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in the Toll-Like Receptor 3 and CD44 Genes Are Associated with Persistence of Vaccine-Induced Immunity to the Serogroup C Meningococcal Conjugate Vaccine

Abstract: fThe rate of decay of antibody concentration following serogroup C meningococcal (MenC) polysaccharide-protein conjugate vaccination varies between individuals. This depends partly on vaccination age but may be influenced by human genetics. We studied 721 single nucleotide polymorphisms (SNPs) across 131 candidate genes in a first cohort of 905 Caucasians (11 to 21 years old; mean time after vaccination, 4.9 years) and 30 SNPs across 17 genes in a replication study using 155 children, aged 6 to 12 years (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…One mechanism identified with variations in humoral (150,(174)(175)(176)(177)(178)(179)(180)(181)(182)(183)(184)(185)(186)(187)(188)(189)(190) and cellular (145,150,186,191) vaccine responses is polymorphism in major histocompatibility complex (MHC) genes (summarized in Table 3). Further genetic factors are polymorphisms in pattern recognition receptors (PRRs), such as Toll-like receptor (TLR) or RIG-like receptor (RLR) genes (192)(193)(194)(195) (Table 3). In addition, many single-nucleotide polymorphisms (SNPs) in other genes, for example, those coding for cytokines or cytokine, viral, or vitamin receptors, are also associated with variations in vaccine responses (182,190,192,193,(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)…”
Section: Lower Vaccine Responses In Neonates and Young Infantsmentioning
confidence: 99%
See 2 more Smart Citations
“…One mechanism identified with variations in humoral (150,(174)(175)(176)(177)(178)(179)(180)(181)(182)(183)(184)(185)(186)(187)(188)(189)(190) and cellular (145,150,186,191) vaccine responses is polymorphism in major histocompatibility complex (MHC) genes (summarized in Table 3). Further genetic factors are polymorphisms in pattern recognition receptors (PRRs), such as Toll-like receptor (TLR) or RIG-like receptor (RLR) genes (192)(193)(194)(195) (Table 3). In addition, many single-nucleotide polymorphisms (SNPs) in other genes, for example, those coding for cytokines or cytokine, viral, or vitamin receptors, are also associated with variations in vaccine responses (182,190,192,193,(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)…”
Section: Lower Vaccine Responses In Neonates and Young Infantsmentioning
confidence: 99%
“…Further genetic factors are polymorphisms in pattern recognition receptors (PRRs), such as Toll-like receptor (TLR) or RIG-like receptor (RLR) genes (192)(193)(194)(195) (Table 3). In addition, many single-nucleotide polymorphisms (SNPs) in other genes, for example, those coding for cytokines or cytokine, viral, or vitamin receptors, are also associated with variations in vaccine responses (182,190,192,193,(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)(209)(210)(211) (Table 3). Further, different expression levels of genes also influence vaccine responses.…”
Section: Lower Vaccine Responses In Neonates and Young Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the numerous data demonstrating alteration of TLR mRNA expression by ligand activation, few reports demonstrated the consequence or specific mechanism by which TLRs themselves are transcriptionally regulated. In addition, the importance of TLR transcriptional regulation is highlighted by the fact that several single nucleotide polymorphisms in TLR promoters predispose humans to several autoimmune and chronic inflammatory diseases, including asthma and Crohn's disease (44)(45)(46)(47)(48)(49)(50)(51). In this article, we provided novel insights on the transcriptional regulation of TLR9 with dsDNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the low sensitivity of these assays, it is possible that TLR signaling may be occurring and not detected through standard assays. Of note, Moore et al have recently identified that SNPs in TLR3 and CD44 genes are associated with persistence of antibody to serogroup C meningococcal conjugate vaccine in a cohort of healthy children aged 6 to 12 years (18). TLR3 recognizes double-stranded RNA through the N-terminal ectodomains; thus, how TLR3 might alter long-term antibody response to meningococcal vaccines is similarly unclear.…”
Section: Discussionmentioning
confidence: 99%